An economic fault-tolerant transportation strategy for multiple assembly station systems*. Issue 10 (2022) - Witczak, Marcin; Seybold, Lothar; Lipiec, Bogdan; Aubrun, Christophe; Mrugalski, Marcin
Abstract: The paper deals with the development of a proof of concept pertaining to the application of Internet of Things tools to the multiple assembly station system. In particular, the problem is to provide efficient measures of an assembly efficiency, which are transformed into material demand predictions. As a result, such predictions are used to form suitable transportation events, which are realized through the shortest possible rout. Thus, instead of providing a periodical milk-run over all assembly stations economic routs are selected instead, which translates into significant savings. Since transportation delays are inevitable in practice, they can be perceived as faults acting onto the system. To overcome such unappealing effect a suitable fault-tolerant control algorithm is provided. Finally, the proposed approach is evaluated with a set of selected scenarios, which clearly illustrate the benefits of employing Internet of Things tools coupled with suitable decision and optimization strategies.